(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article analyzes the characteristics of the supply structure based on the comparison of the stages of solving physical and engineering problems in the preparation of engineers for professional activities. The tasks of the developed teaching-methodical support in the educational process are presented.